Immune system and obsessive-compulsive disorder - Marazziti, Donatella; Mucci, Federico; Fontenelle, Leonardo F. (Psychoneuroendocrinology, 2018)
•Alterations of immune system were described in several neuropsychiatric disorders.•Immune-related diseases are more common in OCD than in other psychiatric disorder.•Immune system could prove to be a potential target for anti-obsessional drugs. Recently, much attention has been devoted to the possible alterations of the immune system in obsessive-compulsive disorder (OCD). Therefore, the aim of this paper was to review the current literature on the relationships between OCD and immune system. A PubMed and Google Scholar search was performed with specific keywords. In the childhood, much emphasis has been given to the relationship between group A Streptococcus (GAS) infection and the development of a group of clinical syndromes characterized by neuropsychiatric symptoms known as “pediatric autoimmune neuropsychiatric disorders associated with streptococcus” (PANDAS). However, more recently, PANDAS has been reconsidered and evolved towards pediatric acute-onset neuropsychiatric syndrome (PANS) and/or Childhood Acute Neuropsychiatric Syndrome (CANS) all characterized by the presence of typical of OCD symptoms and tics. In adult OCD patients, different immunological parameters have been described to differ from those of healthy control subjects, although a few numbers of studies were carred out and most of them performed in small samples. Although the exact relationships between OCD and immune processes are still unclear, available literature supports their role in the pathophysiology of OCD, while providing a fascinating hint for possible immunotherapeutic treatments in OCD.